Dynamic SARS-CoV-2-Specific Immunity in Critically Ill Patients With Hypertension - Zeng, Qiang; Li, Yong-Zhe; Dong, Sheng-Yong; Chen, Zong-Tao; Gao, Xiang-Yang; Zhang, Han; Huang, Gang; Xu, Yang (Frontiers in Immunology, 2020)
Background: The current outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses an unprecedented health crisis. The most common chronic illness among patients infected with SARS-CoV-2 is hypertension. Immune dysregulation plays an important role in SARS-CoV-2 infection and in the development of hypertension; however, the dynamic immunological characteristics of COVID-19 patients with hypertension remain largely unclear. Methods: In total, 258 hypertensive patients infected with SARS-CoV-2 were included in this study. CD38+HLA-DR+ and CD38+PD-1+ CD8+ T cells, IFNγ+CD4+ and IFNγ+CD8+ T cells, the titers of IgG, IgM, and IgA against SARS-CoV-2 spike protein, and SARS-CoV-2 throat viral loads were measured weekly over 4 weeks after the onset of symptoms. Clinical outcomes were also monitored. Findings: CD4+ T lymphopenia was observed in 100% of the severe and critical cases. Compared with the surviving patients, the patients with fatal outcomes exhibited high and prolonged expression of CD38+HLA-DR+ andCD38+PD-1+ on CD8+ T cells, low expression of SARS-CoV-2-specific IFNγ+CD4+ and IFNγ+CD8+ T cells, low titers of IgG, IgM, and IgA against SARS-CoV-2 spike protein, and high SARS-CoV-2 viral load during the illness. In the surviving patients, the viral load was significantly inversely correlated with SARS-CoV-2-specific IFNγ+CD8+and IFNγ+CD4+T cells, IgG, IgM, and IgA. Interpretation: T lymphopenia is common in critical or severe COVID-19 cases with hypertension. Prolonged activation and exhaustion of CD8+ T cells were associated with severe disease. The delayed SARS-CoV-2-specific antibody responses may be insufficient for overcoming severe SARS-CoV-2 infection in the absence of SARS-CoV-2-specific cellular responses.